2016
DOI: 10.1016/j.jpowsour.2016.09.118
|View full text |Cite
|
Sign up to set email alerts
|

A new graphene composite with a high coulombic efficiency

Abstract: Zinc-graphene composite has been electrolytically produced for the first time using a graphene quantum dot (GQD) electrode. The electrochemical reduction of zinc ion at a GQD electrode is shifted to a lesser negative potential with the complimentary anodic peak due to the oxidation of the composite shifted towards a positive potential as compared to zinc ion reduction in the GQD bath. The coulombic efficiency of the composite represents a gain of nearly 10% over the conventional Zn/Zn 2+ in the energy storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…In 2016, an early work reported by Santhanam et al confirmed that graphene quantum dots (GQDs) could combine with zinc metal after electrochemical deposition, which achieved higher coulombic efficiency with zinc flakes rather than dendrites. [ 79 ] Following studies illustrated that graphene materials could serve as current collectors or protective AILs for zinc anodes because of their excellent conductivity and various functional groups.…”
Section: Graphenementioning
confidence: 99%
“…In 2016, an early work reported by Santhanam et al confirmed that graphene quantum dots (GQDs) could combine with zinc metal after electrochemical deposition, which achieved higher coulombic efficiency with zinc flakes rather than dendrites. [ 79 ] Following studies illustrated that graphene materials could serve as current collectors or protective AILs for zinc anodes because of their excellent conductivity and various functional groups.…”
Section: Graphenementioning
confidence: 99%
“…Figure 16 gives the plot of CV peak current vs norovirus concentration. Graphene which has been established to have fast electron transfer property and high chemical stability (Protich, Santhanam, et al, 2016; Protich, Wong, et al, 2016; Wong et al, 2018) was used for constructing real‐time rapid sensor for the pathogenic rotavirus. The specific rotavirus antibodies are covalently attached to the graphene surface after adsorbing 1‐pyrenebutyric acid N‐hydroxy‐succinimide ester through pi‐pi interaction.…”
Section: Review Of the Resultsmentioning
confidence: 99%
“…7647-14-5, ACS, 100 wt %] and Sodium sulfate anhydrous [CAS 7757-82-6, ACS grade, 99.99%] were procured from EMD Millipore Company. Graphene quantum dots were prepared as reported in the literature [24][25][26][27]. The sample conformed to the specifications of graphene given in the earlier publications from Raman spectrum, FTIR and UV-VIS spectrum.…”
Section: Methodsmentioning
confidence: 99%